Precise localization of metal nanoparticles in dendrimer nanosnakes or inner periphery and consequences in catalysis - Liu, Xiang; Gregurec, Danijela; Irigoyen, Joseba; Martinez, Angel; Moya, Sergio; Ciganda, Roberto; Hermange, Philippe; Ruiz, Jaime; Astruc, Didier (Nature Communications, 2016)
Understanding the relationship between the location of nanoparticles (NPs) in an organic matrix and their catalytic performances is essential for catalyst design. Here we show that catalytic activities of Au, Ag and CuNPs stabilized by dendrimers using coordination to intradendritic triazoles, galvanic replacement or stabilization outside dendrimers strongly depends on their location. AgNPs are found at the inner click dendrimer periphery, whereas CuNPs and AuNPs are encapsulated in click dendrimer nanosnakes. AuNPs and AgNPs formed by galvanic replacement are larger than precursors and only partly encapsulated. AuNPs are all the better 4-nitrophenol reduction catalysts as they are less sterically inhibited by the dendrimer interior, whereas on the contrary CuNPs are all the better alkyne azide cycloaddition catalysts as they are better protected from aerobic oxidation inside dendrimers. This work highlights the role of the location in macromolecules on the catalytic efficiency of metal nanoparticles and rationalizes optimization in catalyst engineering.
CRIS-Team Scopus Importer:2020-10-13